Listening as an enunciative strategy (Orfeu, 2024)
This article proposes a critical analy-sis on the premises that embodies recent materialist ontological theories from the sound studies field. We selected the texts of Christoph Cox and Salomé Voegelin as objects of study. First, we presente some authors who investigate the sound and the listening through historical-social ele-ments. Subsequently, we analyzed the the-oretical discourses representative of Cox and Voegelin’s approaches. We compared the authors’ statements to an illustration of pieces and sound characteristics. In order to locate the limits and the problems of the approaches, we seek to understand them through foucauldian notions of discursive practice and enunciative modality.
Keywords: sound studies; listening; power relations; discourse analysis